Dynamics of Islamic Education Supervision: Professionalism and Structural Formality in Private Madrasah - Chandra Dewi (STAI Serdang Lubuk Pakam, 2025)
This study examines the effectiveness of Islamic education supervision at MTs Swasta Ummi Lubuk Pakam, which has tended to be understood as an administrative routine rather than a means of developing teacher professionalism. The purpose of this study is to analyze internal factors such as the competence of the madrasah principal, supervisors, and teachers, as well as external factors in the form of institutional policies and resource availability that affect the effectiveness of supervision, while identifying obstacles in its implementation. This study uses a qualitative approach with a case study method through interviews, observations, and documentation of the madrasah principal, education supervisors, and teachers. The results show that the implementation of supervision in madrasahs is still dominated by an administrative culture, time constraints, and a lack of understanding of the essence of supervision, thus failing to have a significant impact on improving teacher competence. The implications of this study emphasize the importance of transforming the paradigm of Islamic education supervision to be more oriented towards collaborative and sustainable teacher professionalism development in order to improve the quality of learning in private madrasahs